Mechanical performance and material characterization of secondary aluminum alloys for automotive megacasting - Yang, Jihui; Banavathi Marutisha, Nithin Teja (My University, 2025)
The transition toward sustainable automotive manufacturing has intensified interest in using recycled materials without compromising mechanical performance. This thesis investigates the feasibility of applying secondary aluminum alloys in highpressure die casting (HPDC), specifically within the megacasting process for large structural components. Four alloy batches were analyzed: one primary aluminum used as the reference (A4), one secondary aluminum with similar chemical composition (B1), and two secondary aluminum variants with different levels of Fe, Cu, Zn, and V (B2–B3). Mechanical performance was evaluated through tensile, three-point bending, and hardness testing, while microstructural analysis, including optical microscopy, metallography, SEM, and X-ray was used to identify shrinkage, porosity, and intermetallic phases. The results show that recycled aluminum with up to 90% secondary content (B1) can achieve comparable mechanical properties to primary aluminum (A4) when chemical composition remains unchanged. Batches with higher Fe content (B2, B3) exhibited increased yield strength due to solid solution and precipitation strengthening but showed reduced ductility and bending toughness, particularly in regions with greater shrinkage. Comparing the results with historical trials can separate the impact of cast processing and raw material. Microstructural analysis confirmed that casting position influences defect formation and performance. In HPDC, areas farther from the ingate (e.g. F3) generally experience longer flow paths and therefore tend to form more shrinkage and intermetallic phases. Building on this context, this work demonstrates that, with optimized chemistry and process parameters, secondary aluminum alloys can achieve mechanical performance compared with primary alloys, thereby offering a sustainable megacasting solution for the automotive industry.
Keywords: High-pressure die casting (HPDC); Secondary aluminum; Megacasting; Mechanical performance; Microstructure; Sustainability; Automotive manufacturing